2023
DOI: 10.3390/gels9050403
|View full text |Cite
|
Sign up to set email alerts
|

New Photocrosslinked 3D Foamed Scaffolds Based on GelMA Copolymers: Potential Application in Bone Tissue Engineering

Abstract: The production of customized polymeric hydrogels in the form of 3D scaffolds with application in bone tissue engineering is currently a topic of great interest. Based on gelatin methacryloyl (GelMa) as one of the most popular used biomaterials, GelMa with two different methacryloylation degrees (DM) was obtained, to achieve crosslinked polymer networks by photoinitiated radical polymerization. In this work, we present the obtention of new 3D foamed scaffolds based on ternary copolymers of GelMa with vinylpyrro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…However, we discovered that the 5 ng/mL VEGF condition exhibited a tendency to sustain absorbed water over time compared to the other conditions. These results confirm the capacity of the functionalized material (5 ng/mL of VEGF) to maintain sufficiently high swelling values for its application as a cytocompatible biomaterial [ 44 ]. This rich water content provides a physical environment similar to that of native tissue, thus offering an intimate environment for cells to reside and grow [ 45 ].…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…However, we discovered that the 5 ng/mL VEGF condition exhibited a tendency to sustain absorbed water over time compared to the other conditions. These results confirm the capacity of the functionalized material (5 ng/mL of VEGF) to maintain sufficiently high swelling values for its application as a cytocompatible biomaterial [ 44 ]. This rich water content provides a physical environment similar to that of native tissue, thus offering an intimate environment for cells to reside and grow [ 45 ].…”
Section: Resultssupporting
confidence: 70%
“…This confirmed the stability of the hydrogels as a function of the applied frequency. In addition, the behavior of glassy solids is established with a typical oscillatory response for a gel-like material with a covalent polymer network formed by crosslinking PEGDA chains with a physically crosslinked collagen network [ 16 , 42 , 44 ]. These results confirm that the variation in the composition of hydrogels affects their deformation and flow, resulting in tunable materials [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not find statistically significant differences between the groups (p > 0.05), but there was a tendency for the 3 and 5 ng/mL VEGF conditions to have a greater water absorption capacity than the 2 mg/mL and 1 ng/mL VEGF conditions. This characteristic is a key parameter because a high degree of swelling makes them excellent candidates for highly biocompatible materials [44]. After eight days of culture, we found that the 5 ng/mL VEGF condition had a high swelling ratio (16.077 ± 1.178).…”
Section: Swelling and Degradation Ratementioning
confidence: 87%